b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ Strip Symbols Proof
↳ DependencyPairsProof
↳ QTRS Reverse
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
b(a(b(b(a(b(a(b(b(b(x)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x)))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ Strip Symbols Proof
↳ DependencyPairsProof
↳ QTRS Reverse
b(a(b(b(a(b(a(b(b(b(x)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x)))))))))))))
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
b(b(a(b(a(b(b(a(b(x1))))))))) → b(a(b(a(b(b(b(a(b(a(b(b(x1))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ Strip Symbols Proof
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
b(b(a(b(a(b(b(a(b(x1))))))))) → b(a(b(a(b(b(b(a(b(a(b(b(x1))))))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(x1))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(a(b(a(b(b(x1)))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(b(a(b(a(b(b(x1))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(a(b(b(b(a(b(a(b(b(x1))))))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(a(b(b(x1))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(b(x1))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(b(b(a(b(a(b(b(x1))))))))))
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ Strip Symbols Proof
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(x1))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(a(b(a(b(b(x1)))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(b(a(b(a(b(b(x1))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(a(b(b(b(a(b(a(b(b(x1))))))))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(a(b(b(x1))))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(b(x1))))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(a(b(b(b(a(b(a(b(b(x1))))))))))
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ Strip Symbols Proof
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QTRS Reverse
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(x1))
B(b(b(a(b(a(b(b(a(b(x1)))))))))) → B(b(b(a(b(a(b(b(x1))))))))
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
b(b(b(a(b(a(b(b(a(b(x1)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x1)))))))))))))
b(a(b(b(a(b(a(b(b(b(x)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x)))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ Strip Symbols Proof
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ Strip Symbols Proof
b(a(b(b(a(b(a(b(b(b(x)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x)))))))))))))
b(a(b(b(a(b(a(b(b(b(x)))))))))) → b(b(a(b(a(b(b(b(a(b(a(b(b(x)))))))))))))
a(b(b(a(b(a(b(b(b(x))))))))) → b(a(b(a(b(b(b(a(b(a(b(b(x))))))))))))
↳ QTRS
↳ QTRS Reverse
↳ Strip Symbols Proof
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ Strip Symbols Proof
↳ QTRS
↳ RFCMatchBoundsTRSProof
a(b(b(a(b(a(b(b(b(x))))))))) → b(a(b(a(b(b(b(a(b(a(b(b(x))))))))))))
a(b(b(a(b(a(b(b(b(x))))))))) → b(a(b(a(b(b(b(a(b(a(b(b(x))))))))))))
The certificate consists of the following enumerated nodes:
450, 451, 462, 461, 459, 460, 457, 458, 456, 455, 453, 454, 452, 473, 472, 470, 471, 468, 469, 467, 466, 464, 465, 463, 484, 483, 481, 482, 479, 480, 478, 477, 475, 476, 474, 495, 494, 492, 493, 490, 491, 489, 488, 486, 487, 485
Node 450 is start node and node 451 is final node.
Those nodes are connect through the following edges: